Pengembangan Video Pembelajaran Berbasis Canva "PEKSI" tentang Etika Kegiatan Jual Beli pada Pembelajaran PAI Kelas 3 SD - Mulyani, Yurianda; Ananta, Serli; Pramesti, Sekar Ayu Dyah; Aeni, Ani Nur (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The development of a Canva-based learning video regarding the ethics of buying and selling activities in Islamic Religious Education (PAI) learning for grade 3 elementary school students aims to create interesting and interactive media. In an educational context that increasingly demands innovation, using the Canva application allows teachers to present material more visually and easily understood by children. This research uses the D&D (Design and Development) method by applying the ADDIE development model which includes needs analysis, design, development, implementation and evaluation. The results of this development show that the resulting learning videos not only increase students' understanding of the ethics of buying and selling in Islam, but also increase their learning motivation. With an attractive appearance and relevant content, it is hoped that this video can make it easier for students to understand important concepts related to ethical buying and selling in accordance with religious teachings.